1969
DOI: 10.12669/pjms.305.5231
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Kayaking exercises as compared to general mobility exercises in reducing axial rigidity and improve bed mobility in Parkinson’s patients

Abstract: Objective: To determine the effectiveness of kayaking exercises in the management of axial rigidity, improve bed mobility by improving trunk rotation in Parkinson’s patients. Methods: Experimental randomized controlled trail conducted at Physiotherapy department of IPM&R, DUHS and neurology Outpatient Department of Civil Hospital Karachi. Sample size of 48 was calculated with the use of openEpi. After baseline assessment 24 participants were assigned to each Kayaking exercise and general mobility exercise grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Nine RCTs had high methodological quality with scores on the scale equal to or greater than 6: Picelli et al [11], Nimwegen et al [28], Volpe et al [29], Volpe et al [30], Monticone et al [31], Hashimoto et al [32], Rios Romenets et al [33], Volpe et al [34], and Carpinella et al [35]. Shujaat et al [36] and Ricciardi et al [10] scored 5, obtaining the lowest score. [35] 6 _ X X X X X X…”
Section: Assessment Of the Methodological Quality Of The Rcts Includementioning
confidence: 99%
“…Nine RCTs had high methodological quality with scores on the scale equal to or greater than 6: Picelli et al [11], Nimwegen et al [28], Volpe et al [29], Volpe et al [30], Monticone et al [31], Hashimoto et al [32], Rios Romenets et al [33], Volpe et al [34], and Carpinella et al [35]. Shujaat et al [36] and Ricciardi et al [10] scored 5, obtaining the lowest score. [35] 6 _ X X X X X X…”
Section: Assessment Of the Methodological Quality Of The Rcts Includementioning
confidence: 99%
“…Fifteen studies met the inclusion criteria and were included [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]: five RCTs [18,19,[21][22][23], seven non-RCTs [20,25,26,[28][29][30][31], and three CTs with healthy control groups [17,24,27]. The 15 selected studies were published between 2004 and 2021 and enrolled a total of 1045 individuals, comprising 280 men (26.8%) and 645 women (61.7%).…”
Section: Search Results and Qualitative Synthesismentioning
confidence: 99%
“…Of the 15 studies selected, 2 focused on canoa kayak [17,18] 1 on stand-up paddle (SUP) [19], 2 on surfing [20,21], 2 on sailing [22,23], and 8 on dragon boat padding [24][25][26][27][28][29][30][31]. Three studies were conducted in people affected by mental health disorders [21][22][23], seven in cancer survivors (among these, six studies focused on women with breast cancer, BC) [25][26][27][28][29][30][31], one study in patients with cardiac and noncardiac transplants [24], one in children with congenital disabilities [20], two studies in persons with neurological diseases, such as spinal cord injury (SCI) [19] and Parkinson's disease, PD [18], while one enrolled healthy older adults [19]. The median TESTEX score for study quality and reporting was 6/15 (range 5-8), indicating "very low" to "low" methodological quality of the studies.…”
Section: Search Results and Qualitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Since multi-directional movements might induce a subsequent increase in limit of stability, this could significantly improve Functional Reach Test scores. Shujaat et al (2014) suggested that kayaking exercise would improve trunk mobility in patients with Parkinson’s disease [ 29 ]. Granacher et al (2013) found that core instability strength training strengthened trunk muscles and improved spinal mobility, dynamic balance, and functional mobility of older adults [ 30 ].…”
Section: Discussionmentioning
confidence: 99%